Theorizing race, marginalization, and language in the digital media (Communication & Society, 2021)
Digitization of the communication medium has transformed the mute, marginalized ‘audience’ into a heterogeneous and credible content ‘producer.’ Drawing on this dynamics and operation of the digital media, it has urged the need to re-theorize ‘marginalization’ and ‘race.’ Hence, this paper critiques the digital-media tool, blogs, using a rhetoric-textual analysis method and critical discourse analysis method for the fictional text, Americanah. These methods employ the psychoanalytical-Althusserian critique of Adichie’s fictional narrative, Americanah. In the psychoanalytical sense, blog-writing can qualify as a mechanism of ‘sublimation’ in the post-modern world. In the Althusserian sense, blogs become persuasive mechanisms for a subject’s interpellation into non-dominant ideology. Among the plethora of marginalized global communities, African-Americans are enormously embracing the virtual communication trends for socio-political motives. This paper theorizes the correlations between race-related blogging, psychoanalytic sublimation, and the socio-political repudiation of power structure by employing the literary text as material evidence. Accordingly, the literary study has concluded that digital-mediums (i.e., in this case, political blogs) can depose the power vested in the ideological-state-apparatuses and impose a high potential for expression of unrestrained, credible, and democratic voice of the marginalized. It also validates that blogs/blogging influences and moulds national/political/racial discourses by lending a liberated voice and context-independent perspective to the racially oppressed.